Synthesis of Cr(III)-terephthalate metal-organic framework and its application to modify electrodes for electrochemical analysis of paracetamol - Nguyễn, Ngọc Nghĩa; Hồ, Văn Thành; Nguyen, Quang Man (Hue University Journal of Science: Natural Science, 2025)
This study describes the synthesis of a metal-organic framework material MIL (Materials Institute Lavoisier) by using the hydrothermal method. The obtained materials were characterized with X-ray diffraction and scanning electron microscopy. The study shows that MIL-101 was formed at an early stage of synthesis (8 h), and then the phase transformation of the material occurred when the reaction time was extended to 48 h. The octahedral morphology of MIL-101 changed to a rod-like shape when the hydrothermal time increased. An electrode modified with MIL-101 exhibited more satisfied electrochemical properties towards paracetamol than other electrodes via cyclic voltammetry measurements. The differential pulse voltammetry measurements show a high linearity between peak currents and PCT concentration in the concentration range of 0.50–6.95 µM with a detection limit of 0.68 µM.